2020
DOI: 10.1002/ehf2.13044
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic abnormalities and predictors of mortality in hospitalized COVID‐19 patients: the ECHOVID‐19 study

Abstract: Aims The present study had two aims: (i) compare echocardiographic parameters in COVID-19 patients with matched controls and (2) assess the prognostic value of measures of left (LV) and right ventricular (RV) function in relation to COVID-19 related death. Methods and results In this prospective multicentre cohort study, 214 consecutive hospitalized COVID-19 patients underwent an echocardiographic examination (by predetermined research protocol). All participants were successfully matched 1:1 with controls fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
149
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(160 citation statements)
references
References 27 publications
6
149
1
4
Order By: Relevance
“…In a sub-group analysis, RV dysfunction and elevated PAP were independently associated with an increased risk of death. This is consistent with ndings from other studies of patients with ARDS and hospitalized patients with COVID-19 [13,14]. Regrettably, the main cause of death was not registered in the present study, and patients were not systematically assessed for pulmonary embolism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a sub-group analysis, RV dysfunction and elevated PAP were independently associated with an increased risk of death. This is consistent with ndings from other studies of patients with ARDS and hospitalized patients with COVID-19 [13,14]. Regrettably, the main cause of death was not registered in the present study, and patients were not systematically assessed for pulmonary embolism.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac complications, on a case report basis, include myocarditis [8][9][10], COVID-19 associated Takotsubo cardiomyopathy [11,12], and myocardial infarction [12]. Several studies have reported abnormalities in left and right ventricular function in a large proportion of patients with COVID-19 undergoing echocardiography [12][13][14][15]. Studies have also shown that left and right ventricular dysfunction are independently correlated to increased mortality in patients with COVID-19 [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in COVID-19 with or without critical illness have suggested an association between markers of RV/LV dysfunction and COVID-19 related death [ 26 , 27 ]. In our work, no association was found between 28-day mortality and echocardiographic variables, except for lower E/A values in non-survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Routine echocardiography is also useful in critical care settings. Global longitudinal strain (GLS) measurement provides direct measurement of myocardial deformation; thus, it is less affected by different loading conditions compared to ejection fraction [4]. Ventricular strain has been shown to be a useful tool for prognostication in patients with acute respiratory distress syndrome (ARDS) [5].…”
Section: Introductionmentioning
confidence: 99%